Factors Affecting the Financial Performance of MSMES: Financial Literacy, Financial Inclusion, Financial Self-Efficacy, Financial Technology, Credit Granting, and Intellectual Capital - Christine, Christine; Zukhri, Nizwan; Saputra, Darman (Almana : Jurnal Manajemen dan Bisnis, 2024)
MSMEs are one of the economic icons that have the biggest impact on Indonesia's economic growth, especially when a crisis occurs. MSMEs are able to get through monetary crises such as in 1998 and during the Covid-19 pandemic. MSMEs are independent and have great potential to improve community welfare. This research aims to examine the influence of the variable’s financial literacy, financial inclusion, financial self-efficacy, financial technology, credit granting, and intellectual capital on the financial performance of MSMEs in the Bangka Belitung Islands Province. This research is quantitative research with an associative method using a quantitative approach from primary data through distributing questionnaires. The sampling method was nonprobability sampling with a purposive sampling technique so that 102 MSME actors were obtained. The data analysis technique uses SPSS version 26 software. The research results prove that partial financial inclusion (X2), financial technology (X4), credit granting (X5), and intellectual capital (X6) have a positive and significant effect on the financial performance of MSMEs, while financial literacy (X1) and financial self-efficacy (X3) do not have a positive and significant effect on the financial performance of MSMEs. Simultaneously, the variables financial literacy, financial inclusion, financial self-efficacy, financial technology, credit granting, and intellectual capital have a positive and significant effect on the financial performance of MSMEs in the Bangka Belitung Islands. The R Square value in this research is 0.885, so it is concluded that 88.5% of the variation in the dependent variable can be explained by the independent variable and the remaining 11.5% is influenced by other variables not examined in this research. It is hoped that the research results can become reference material and motivation for MSMEs in improving the financial performance of their businesses.